Konfigurasi Filantropi Islam Era Digital: Efektifitas Infaq Melalui Situs Kitabisa.com Sebagai Crowdfunding Di Indonesia - Kurnia Anisa, Lutfiani; Kurniawan, Nauval (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2023)
Crowdfunding is defined as an open call or offer accessed via the Internet for the provision of financial resources either in the form of donations or otherwise. The study was carried out with a qualitative approach through library research. Data collection techniques with documentation studies and data processing with reduction and presentation of data. The results of the discussion show: the implementation of digital Islamic philanthropy through the Kitabisa.com website can increase the effectiveness of giving donations from donors to those who need donations and by continuing to innovate by adding attractive features in order to make it easier for donors to make donations and by improving the security system and management of its operations.